cis requirements for the efficient production of recombinant DNA vectors based on autonomous parvoviruses - Kestler, Jürgen Werner; Rommelaere, Jean; Dinsart, Christiane (Human gene therapy, 2004)
The replication of viral genomes and the production of recombinant viral vectors from infectious molecular clones of parvoviruses MVMp and H1 were greatly improved by the introduction of a consensus NS-1 nick site at the junction between the left-hand viral terminus and the plasmid DNA. Progressive deletions of up to 1600 bp in the region encoding the structural genes as well as insertions of foreign DNA in replacement of those sequences did not appreciably affect the replication ability of the recombinant H1 virus genomes. In contrast, the incorporation of these genomes into recombinant particles appeared to depend on in cis-provided structural gene sequences. Indeed, the production of H1 viral vectors by cotransfection of recombinant clones and helper plasmids providing the structural proteins (VPs) in trans, drastically decreased when more than 800 bp was removed from the VP transcription unit. Furthermore, titers of viral vectors, in which most of the VP-coding region was replaced by an equivalent-length sequence consisting of reporter cDNA and stuffer DNA, were reduced more than 50 times in comparison with recombinant vectors in which stuffer DNA was not substituted for the residual VP sequence. In addition, viral vector production was restricted by the overall size of the genome, with a mere 6% increase in DNA length leading to an approximately 10 times lower encapsidation yield. Under conditions fulfilling the above-mentioned requirements for efficient packaging, titers of virus vectors from improved recombinant molecular DNA clones amounted to 5 X 10 7 infectious units per milliliter of crude extract. These titers should allow the assessment of the therapeutic effect of recombinant parvoviruses expressing small transgenes in laboratory animals.
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.02.2021